1987
DOI: 10.1111/j.1365-2362.1987.tb01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodic courses of human 1–34 parathyroid peptide alternating with calcitriol paradoxically reduce bone remodelling in spinal osteoporosis

Abstract: In an attempt to achieve an anabolic response in both axial and peripheral bone, we treated twelve patients with osteoporosis using human 1-34 parathyroid peptide given discontinuously. The peptide was given as seven daily subcutaneous injections followed by 21 days' treatment with 0.25 mg calcitriol orally. This regime was repeated cyclically for at least sixteen cycles, of which the first four were at a lower dose of hPTH 1-34 than used subsequently. The results of treatment were monitored by kinetic, densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Although in hyperparathyroidism this catabolic effect leads to loss of bone mineral content, PTH has an anabolic effect on bone remodeling when administered intermittently 78. Teriparatide (1–34 amino acid peptide) is a human PTH analog which also has an osteoanabolic effect when administered intermittently at low doses 79. Teriparatide (Forteo ® ) is effective (20 μg/day subcutaneously) at increasing BMD in postmenopausal and glucocorticoid-induced osteoporosis and is more effective than alendronate at reducing the incidence of vertebral and hip fractures 8082.…”
Section: Current Therapeutic Management Options For Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Although in hyperparathyroidism this catabolic effect leads to loss of bone mineral content, PTH has an anabolic effect on bone remodeling when administered intermittently 78. Teriparatide (1–34 amino acid peptide) is a human PTH analog which also has an osteoanabolic effect when administered intermittently at low doses 79. Teriparatide (Forteo ® ) is effective (20 μg/day subcutaneously) at increasing BMD in postmenopausal and glucocorticoid-induced osteoporosis and is more effective than alendronate at reducing the incidence of vertebral and hip fractures 8082.…”
Section: Current Therapeutic Management Options For Osteoporosismentioning
confidence: 99%
“…The administration of raloxifene prior to teriparatide improves BMD above that of teriparatide alone 83. In open-label studies, alendronate blunted the ability of teriparatide to increase BMD when the therapies were combined,79 whereas in another study patients that had been previously treated with risedronate showed better improvement in BMD in response to teriparatide than patients that had previously been on alendronate therapy 8484.…”
Section: Current Therapeutic Management Options For Osteoporosismentioning
confidence: 99%